Learning and teaching at M-level : a guide for student teachers - Bryan, Hazel; Hoult, Simon; Carpenter, Chris (Los Angeles ; London : SAGE, 2010)
This text guides readers through the different aspects of doing M-level work at either primary or secondary stage, & helps to develop a deeper professional understanding. Chapters include primary & secondary vignettes & examples to link theory into practice, as well as questions, activities & suggestions for further reading.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Education -- Study and teaching (Graduate) -- Great Britain; Electronic books